1968
DOI: 10.1111/j.1348-0421.1968.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference with Virus Infection Induced by RNA in Chick Embryo Cells

Abstract: Some single-stranded RNA's, notably RNA from E. coli bacteriophage MS2, were found to induce interference with viral growth (Sindbis, vesicular stomatitis, and vaccinia viruses) in chick embryo cell culture. Oligonucleotides appear to have a more essential role for induction of interference than high molecular weight RNA, since (a) phage RNA preparations containing degraded components are more consistently effective than preparations consisting essentially of intact molecules, (b) chick embryo RNA (homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
1

Year Published

1969
1969
1980
1980

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…We have independently observed that, not only double-stranded RNAs, but also some kinds of single-stranded RNAs, and oligonucleotides may also interfere with virus multiplication in chick embryo cell cultures [4,5]. The relationship between our findings and those of other workers on doublestranded RNAs is not yet clear, though they may possibly be closely related, and we have investigated the further characterization of the interference phenomenon caused by single-and double-stranded RNAs in chick cells.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…We have independently observed that, not only double-stranded RNAs, but also some kinds of single-stranded RNAs, and oligonucleotides may also interfere with virus multiplication in chick embryo cell cultures [4,5]. The relationship between our findings and those of other workers on doublestranded RNAs is not yet clear, though they may possibly be closely related, and we have investigated the further characterization of the interference phenomenon caused by single-and double-stranded RNAs in chick cells.…”
mentioning
confidence: 83%
“…Interferon induced in chick cell cultures by infection with SbV was used. The details have been described in our previous paper [4].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations